A scientometric analysis of quantity surveying research: trends and future direction - Taiwo Adegbembo; Douglas Aghimien (Journal of Construction Project Management and Innovation)
The development of people, organisations and professions is driven by several factors including research. As such, evaluating research trends within a given field of study is necessary to understand current issues and identify gaps to make meaningful contributions to the body of knowledge. The scientometric analysis offers the opportunity to understand these research trends while identifying leading contributors (authors, countries, institutions), impactful contributions and areas of focus in existing studies. Using the scientometric analysis, this paper presents a visualisation of quantity surveying (QS) research published from 2003 to 2023 and indexed in the Scopus database. Using an interpretivist philosophical stance, the study found that QS studies have emanated from diverse countries, including the United Kingdom, Malaysia, Nigeria, South Africa and Australia. Journal outlets are the major sources of disseminating QS research findings, while the lack of proper indexing of many QS conference proceedings is responsible for fewer conference publications. Past QS studies have focused on six major areas, which are (1) QS professional service and management, (2) QS and BIM in design and cost estimating, (3) QS competencies, (4) QS education and training, (5) QS in the construction industry, (6) QS and project planning. These identified areas create room for future studies to research less explored areas such as human resource management, higher education, information theory, QS and climate change adaptation, green/circular/bio-economy, digitalisation, and innovative construction.